Ionic Liquid 1-Octyl-3-Methylimidazolium (M8OI) Is Mono-Oxygenated by CYP3A4 and CYP3A5 in Adult Human Liver - Alistair C. Leitch; Tarek M. Abdelghany; Alex Charlton; Martin Cooke; Matthew C. Wright (Journal of Xenobiotics)
Environmental sampling around a landfill site in the UK previously identified the methylimidazolium ionic liquid, 1-octyl-3-methylimidazolium (M8OI), in the soil. More recently, M8OI was shown to be detectable in sera from 5/20 PBC patients and 1/10 controls and to be oxidised on the alkyl chain in the human liver. The objective of this study was to examine the metabolism of M8OI in humans in more detail. In human hepatocytes, M8OI was mono-oxygenated to 1-(8-Hydroxyoctyl)-3-methyl-imidazolium (HO8IM) then further oxidised to 1-(7-carboxyheptyl)-3-methyl-1H-imidazol-3-ium (COOH7IM). The addition of ketoconazole—in contrast to a range of other cytochrome P450 inhibitors—blocked M8OI metabolism, suggesting primarily CYP3A-dependent mono-oxygenation of M8OI. Hepatocytes from one donor produced negligible and low levels of HO8IM and COOH7IM, respectively, on incubation with M8OI, when compared to hepatocytes from other donors. This donor had undetectable levels of CYP3A4 protein and low CYP3A enzyme activity. Transcript expression levels for other adult CYP3A isoforms—CYP3A5 and CYP3A43—suggest that a lack of CYP3A4 accounted primarily for this donor’s low rate of M8OI oxidation. Insect cell (supersome) expression of various human CYPs identified CYP3A4 as the most active CYP mediating M8OI mono-oxygenation, followed by CYP3A5. HO8IM and COOH7IM were not toxic to human hepatocytes, in contrast to M8OI, and using a pooled preparation of human hepatocytes from five donors, ketoconazole potentiated M8OI toxicity. These data demonstrate that CYP3A initiates the mono-oxygenation and detoxification of M8OI in adult human livers and that CYP3A4 likely plays a major role in this process.